Hungarian Monitoring, 2 July 1989 . [Magyar rádiófigyelő], 1989. július 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - American representative of Hungarian origin Tom Lantos thinks a new Marshall Plan should not be expected from Moscow - Josef von Ferenczy: following personnel changes at the top levels in Hungarian Socialist Workers' Party (MSZMP), Hungary may receive Western help sooner Domestic Affairs: - Archbishop László Paskai and young Hungarian believers take part in international ecumenical conference in Munich - Conversation with Sándor Zágor on post-56 slanders - Interview with György Konrád - Interview with Sándor Csoóri and István Csurka - War of conflicting statements continues between two wings of Hungarian Social Democratic Party Economy: - Temporary break in improving the Hungarian balance of payments this year, says Rezső Nyers at economists' traveling seminar in Szombathely Külpolitika: - Tom Lantos magyar származású amerikai képviselő szerint nem lehet egy ú Marshall-tervet várni Washingtontól - Josef von Ferenczy szerint az MSZMP élén történt személyi változások nyomán Magyarország hamarabb kaphat nyugati gazdasági segítséget Belpolitika: - Paskai László érsekkel hívő magyar fiatalok is részt vesznek a müncheni nemzetközi ökomenikus találkozón - Beszélgetés Zágor Sándorral 56 utáni meghurcoltatásáról - Interjú Konrád Györggyel - Interjú Csoóri Sándorral és Csurka Istvánnal - Folytatódik a nyilatkozat-háború a magyarországi szociáldemokraták két szárnya között Gazdaság: - A magyar fizetési mérleg javításának folyamata az idén átmenetileg megszakad - Mondta Nyers Rezső a szombathelyi közgazdász vándorgyűlésen